Layout Redesign and Area Determination for B3 Waste Temporary Storage at PT XZY in Jababeka Industrial District, West Java - Permatasari, Wahyu Sekti Retno (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The expansion of production capacity in the automotive industry has resulted in a proportional increase in the generation of hazardous and toxic waste. PT XYZ produces seven types of B3 waste as a byproduct of its production and operational activities. This study aims to assess current waste management practices in light of relevant government regulations, identify the types and quantities of B3 waste produced, and develop a redesigned layout for the B3 Waste Temporary Storage Facility (TPS) in accordance with the Minister of Environment and Forestry Regulation No. 6 of 2021. The research methodology includes field observations, interviews, and a redesign of the TPS that complies with the stated regulation. The findings indicate that the company has not yet fully adhered to the applicable regulatory requirements. For instance, the facility's limited building area and inadequate spill containment infrastructure. Therefore, improvements in B3 waste storage practices are necessary. The recommended dimensions for the TPS are 8.79 meters in length, 5.86 meters in width, and 3 meters in height. The spillage container size is suggested to be 0.4 meters long, 0.3 meters wide, and 0.55 meters high.